MSH3 modifies somatic instability and disease severity in Huntington’s and myotonic dystrophy type 1 - Flower, Michael (2019)
Huntington’s disease and myotonic dystrophy type 1. A recent Huntington’s disease genome-wide association study found rs557874766, an imputed single nucleotide polymorphism located within a polymorphic 9 bp tandem repeat in MSH3/DHFR, as the variant most significantly associated with progression in Huntington’s disease. Using Illumina sequencing in Huntington’s disease and myotonic dystrophy type 1 subjects, we show that rs557874766 is an alignment artefact, the minor allele for which corresponds to a three-repeat allele in MSH3 exon 1 that is associated with a reduced rate of somatic CAG CTG expansion (P = 0.004) and delayed disease onset (P = 0.003) in both Huntington’s disease and myotonic dystrophy type 1, and slower progression (P = 3.86 10 7) in Huntington’s disease. RNA-Seq of whole blood in the Huntington’s disease subjects found that repeat variants are associated with MSH3 and DHFR expression. A transcriptome-wide association study in the Huntington’s disease cohort found increased MSH3 and DHFR expression are associated with disease progression. These results suggest that variation in the MSH3 exon 1 repeat region influences somatic expansion and disease phenotype in Huntington’s disease and myotonic dystrophy type 1, and suggests a common DNA repair mechanism operates in both repeat expansion diseases.